2012
DOI: 10.1016/j.aca.2012.04.026
|View full text |Cite
|
Sign up to set email alerts
|

On-line amino acid-based capillary isoelectric focusing-ESI-MS/MS for protein digests analysis

Abstract: Six amino acids with pIs that ranged from 3.2 to 9.7 were used as ampholytes to establish a pH gradient in capillary isoelectric focusing. This amino acid-based capillary isoelectric focusing (cIEF) was coupled with ESI-MS/MS using an electrokinetically pumped sheath-flow interface for peptide analysis. Amino acid-based isoelectric focusing generates a two-order of magnitude lower background signal than commercial ampholytes in the important m/z range of 300–1800. Good focusing was achieved for insulin recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…3A). This result is likely due to ionization suppression of peptides by the amino acids used as ampholytes [30], which lowers the peptides’ charge. The assumption agreed with the relationship between charge and MH + of peptides from the two approaches, S-Fig.3 in supporting material I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). This result is likely due to ionization suppression of peptides by the amino acids used as ampholytes [30], which lowers the peptides’ charge. The assumption agreed with the relationship between charge and MH + of peptides from the two approaches, S-Fig.3 in supporting material I.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that amino acids can act as ampholytes to create the pH gradient in cIEF while generating very low background signals in the m/z range for tryptic peptides [30]. We observed that the background signal intensity generated by the amino acids was a factor of 30 lower than that generated by commercial ampholytes, which was valuable in the study of low abundance peptides by ESI-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Their work is discussed further in the MS detection section of this review. Along with the development of new interfaces, several straightforward BGE buffer modifications have been described in the literature to solve the problems of high backgrounds and ion suppression [63, 64]. …”
Section: Techniquesmentioning
confidence: 99%
“…AAs‐based CIEF of tryptic peptides of BSA with pH gradient formed by six AAs with p I s in the range 3.2–9.7 provided a two‐order lower background signal of ESI‐MS/MS detection than CIEF with commercial polycomponent CAs in the important 300–800 m / z range, resulting in much cleaner mass spectra and higher protein spectral counts. Flattening of pH gradient of CIEF by addition of the particular narrow pH fraction of the CAs to the commercial CAs contributed to the improved resolution of normal and glycated hemoglobins has the potential to enhance also CIEF separation of polypeptides.…”
Section: Separations In Different Ce and Cec Modesmentioning
confidence: 99%